Verification and Validation in Complex Warship Systems Design Process - Odukoya, Adebowale; Duffy, Alex; Whitfield, Ian (Center for Model-Based Cyber-Physical Product Development, 2021)
The modern warship is the most complex man-made system of systems (SoS). Consequently, the required approach to verify and validate the stakeholders’ pre-specified requirements for the system throughout its lifecycle must match the complexity of the warship. An SoS allows for continuous monitoring and control of diverse interdependent systems that provide a complex function, as well as the assurance of confidential exchange of information. In systems engineering, the process of verification and validation is performed at several levels within a system, at the unit level, the integration level and the systems level. Verification at a system level is carried out to ensure all systems work together in a systematic and cohesive way. While validation confirms whether the specification of the requirements have been understood and interpreted in the system accordingly. The verification and validation processes are intended to ensure that the system meets its specification and fulfils the intended purpose, while ensuring the quality of system built and the customer satisfaction with the resulting system. This paper disseminates a centre-out approach towards verification and validation rather than the traditional V model which embraces the divide and conquer approach. The design process requires a more agile approach to the verification and validation of requirements, especially in a complex system such as warship. A model-based approach is taken towards the execution of verification and validation throughout the systems design process. This approach will activate a higher level of agility, iteration and continuous integration of the process model. This will mitigate lack of precision, delayed integration and unexpected emergent behaviour in the Cyber-Physical System (CPS).